Decision Design And Development Of E-Learning For Islamic Studies - Othman, Hasmiza (2010)
Despite the effort by Ministry of Education to promote ICT in education in Malaysia, Islamic education syllabus is way far behind the intended plan in terms of its ICT usage in learning and teaching. It was believed that Islamic studies faced the risk of being misleading or misunderstood if the lessons were taught through self-accessing method with minimal intervention from teacher; a method that e-learning is popular for.